Simultaneous complete supraaortic debranching and thoracic aortic endografting in an angiography suite setting - Geisbüsch, Philipp; Katzen, Barry T.; Moreno, Niberto; Benenati, James F.; Powell, Alex; Tsoukas, Athanassios I.; Garcia, Lisardo (Journal of vascular and interventional radiology, 2011)
This case series reports an initial experience in three patients treated with simultaneous complete supraaortic debranching and thoracic aortic endografting in an angiography suite setting. The article focuses on logistics and structural considerations of the setting. This includes size and equipment of the angiography suite, extent and supply of conventional surgical instruments, and safety considerations. The clinical outcome of the patients is reported. This limited experience shows that simultaneous aortic arch hybrid procedures can be performed in an angiography suite setting, given the structural and logistic requirements described.